Electrochemical Performance of Chemically Activated Carbons from Sawdust as Supercapacitor Electrodes - Meruyert Nazhipkyzy; Mukhtar Yeleuov; Shynggyskhan T. Sultakhan; Anar B. Maltay; Aizhan A. Zhaparova; Dana D. Assylkhanova; Renata R. Nemkayeva (Nanomaterials, 2022)
Activated carbons (ACs) have been the most widespread carbon materials used in supercapacitors (SCs) due to their easy processing methods, good electrical conductivity, and abundant porosity. For the manufacture of electrodes, the obtained activated carbon based on sawdust (karagash and pine) was mixed with conductive carbon and polyvinylidene fluoride as a binder, in ratios of 75% activated carbon, 10% conductive carbon black, and 15% polyvinylidene fluoride (PVDF) in an N-methyl pyrrolidinone solution, to form a slurry and applied to a titanium foil. The total mass of each electrode was limited to vary from 2.0 to 4.0 mg. After that, the electrodes fitted with the separator and electrolyte solution were symmetrically assembled into sandwich-type cell construction. The carbon’s electrochemical properties were evaluated using cyclic voltammetry (CV) and galvanostatic charge–discharge (CGD) studies in a two-electrode cell in 6M KOH. The CV and CGD measurements were realized at different scan rates (5–160 mV s−1) and current densities (0.1–2.0 A g−1) in the potential window of 1 V. ACs from KOH activation showed a high specific capacitance of 202 F g−1 for karagash sawdust and 161 F g−1 for pine sawdust at low mass loading of 1.15 mg cm−2 and scan rate of 5 mV s−1 in cyclic voltammetry test and 193 and 159 F g−1 at a gravimetric current density of 0.1 A g−1 in the galvanostatic charge–discharge test. The specific discharge capacitance is 177 and 131 F g−1 at a current density of 2 A g−1. Even at a relatively high scan rate of 160 mV s−1, a decent specific capacitance of 147 F g−1 and 114 F g−1 was obtained, leading to high energy densities of 26.0 and 22.1 W h kg−1 based on averaged electrode mass. Surface properties and the porous structure of the ACs were studied by scanning electron microscopy, energy-dispersive X-ray analysis, Raman spectroscopy, and the Brunauer–Emmett–Teller method.